From digital play to intercultural belonging: International students’ e-sports participation and social integration in Chinese universities - Cheng, Baicheng; Li, Jiaqi; Shen, Hui (Journal of International Students, 2026)
As digital communities increasingly shape university social life, e-sports has become an overlooked site where international students may enter peer networks and negotiate belonging. This study examines how international students in Chinese universities participate in e-sports communities, develop intercultural relationships, and negotiate identity across digital and campus spaces. Based on semistructured interviews with twelve international students, thematic analysis revealed three interconnected processes that were synthesized as adaptive cross-cultural engagement (ACE): collaborative participation through digital play, interpersonal recognition through collaborative usefulness, and negotiated visibility. Drawing on communities of practice, sense of belonging, and identity negotiation theory as sensitizing lenses, the ACE emerged from the analysis rather than from a predefined framework. It explains how e-sports participation can develop into social integration when access becomes meaningful recognition and cultural difference remains visible within shared practice. This movement remained conditional, as language barriers, unequal feedback, and exclusion could interrupt the transition from participation to belonging.